The ceramide- and phosphatidylcholine- based Coronary Event Risk Test2 (CERT2) and cardiovascular mortality in men and women with type 2 diabetes. (14th October 2021) - Leiherer, A; Muendlein, A; Saely, C H; Larcher, B; Mader, A; Maechler, M; Sprenger, L; Mutschlechner, B; Benda, M; Laaksonen, R; Laaperi, M; Jylha, A; et al.
Abstract: : The recently introduced Coronary Event Risk Test version 2 (CERT2) is a validated cardiovascular risk predictor score that uses circulating ceramide and phosphatidylcholine concentrations. The purpose of this study was to investigate the power of CERT2 to predict cardiovascular mortality in 280 male and 121 female patients with type 2 diabetes (T2DM). Prospectively, we recorded 55 cardiovascular deaths in men and 19 in women during a mean follow-up time of 7.6±3.6 and 8.1±3.4 years respectively. Overall, cardiovascular survival decreased with increasing CERT2 risk categories (figure 1). In Cox regression models, CERT2 significantly predicted the incidence of cardiovascular mortality in male patients with T2DM (unadj. HR 1.82 [1.39–2.37] per standard deviation; p<0.001), the unadj. HR in women was 1.36 [0.83–2.22]; p=0.228). After adjustment for age, BMI, current smoking, LDL cholesterol, HDL cholesterol, hypertension, and statin use the HR in men was 1.73 [1.31–2.29]; p<0.001) and 1.40 [083–2.36]; p=0.210 in women. Interaction terms CERT2 x gender were non-significant both in univariate analysis (p=0.354) and after multivariate adjustment (p=0.359). We conclude that sex does not significantly impact the association of CERT2 with cardiovascular mortality in patients with T2DM. Funding Acknowledgement: Type of funding sources: None.